Best Practice Inovasi Pelayanan Publik “Laboratorium Kemiskinan” Di Kabupaten Pekalongan - Kurniani Wismaningsih; Retno Sunu Astuti; Ida Hayu Dwimawanti; Budi Puspo; Teuku Afrizal (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to examine the best practice of public service innovation "Poverty Laboratory" as an effective and efficient way of completing an activity with a specific, repeatable and useful procedure to implement. Based on the best practice proxies offered by Prasojo in 2007, namely impact, partnership, sustainability, leadership, and transferability to other areas, the research used a descriptive qualitative approach. This research was conducted in Pekalongan Regency. Collecting data using interviews, observation and documentation. The results of the study found that the Poverty Laboratory had met the best practice criteria. With the Poverty Laboratory two of the three model villages have left the category of red villages. The Poverty Laboratory won the award for TOP 45 Innovation in the 2020 National Level Public Service Innovation Competition or better known as SINOVIK. Pekalongan District Government must maintain these achievements, however, in its implementation, a Poverty Laboratory Development Technical Guideline should be prepared which contains, among other things, the details of the amount of funds needed in each model village and what forms of village government support in this program.